Implementação de um ambiente hospitalar lúdico para visita de crianças às mães internadas em uma Unidade Psiquiátrica - Lied, Ricardo Germano (2018)
This study deals with the humanization of care in a psychiatric hospitalization unit, especially through an environment that promotes physical and psychological comfort, considering the importance of affective spaces that require the well-being of the recipient of the health care actions mental health and their families. With the assumptions of the ambience concept, environmental psychology and restorative environments, this dissertation discusses the implementation of a playful space to receive children who visit their mothers during psychiatric hospitalization, considering the concern with the quality of the mother-child relationship in the hospital context. Objectives: To implement a playful hospital environment to children visit their mothers hospitalized in a psychiatric unit; to analyze the benefits and demands for adequacy of the space implemented based on the perception of the hospitalized mothers and the multiprofessional team. Method: This is an action-research carried out from June to October, 2018, in a psychiatric hospitalization unit of a general hospital located in the central region of Rio Grande do Sul. Participants in the study were seven hospitalized mothers, who answered an interview, and 28 professionals from the multiprofessional health team, through a questionnaire. Data from the closed questions were quantitatively evaluated through a descriptive analysis. The material obtained from the open questions had been subjected to qualitative content analysis. Results: About the adequacy of the room, 82% of the professionals considered the room adequate, in the qualitative analysis of the suggestions, the identified need was to increase the physical space. Regarding the implemented environment, 89% of the professionals considered that it will be another therapeutic tool in the treatment of patients with children in the childhood phase. In addition, 89% of the professionals indicated that the use of the room favored the patient's hospitalization. About the interaction at the moment of the visit, 100% of the participant team answered that the patient's experience in the play room "Mania de Brincar" contributed positively to the mother-child interaction. The seven mothers evaluated the use of space as a benefit that produced well-being, contributing positively to the reception of their children. Final considerations: The implemented environment favors the quality of the mother-child interaction during hospital visits, promoting well-being and motivation for the continuity of treatment. The humanized, affective and welcoming environment, created to be a restorative environment, could be an important factor to minimize the psychic suffering of the patient and their relatives, contributing to mental health care. Product: a playful hospital room, built to welcome the visit of children to mothers hospitalized in a psychiatric unit, in a general hospital. Applicability of the product: The product can be used on all weekends when there are mothers with small children hospitalized in the unit. The room can also be refined with the time of use and the experience can be replicated in other units of the hospital and in other hospitals. The environment can also be used to produce other research on the environment-person relationship.